A case report on bilateral neuromyelitis optica - Patel, Abhishek Mansinh; Sheikh, Khushnood M.; Shastri, Manisha B. (International Journal of Research in Medical Sciences, 2016)
Neuromyelitis optica (NMO, Devic disease) is an autoimmune inflammatory disorder of the central nervous system (CNS) in which the autoimmune system attacks myelin of the neurons located at the optic nerve and spinal cord, thus producing a simultaneously or sequential longitudinally extensive inflammation of the optic nerve (optic Neuritis) and spinal cord (myelitis). Early discrimination between NMO and multiple sclerosis is important because the two diseases have different natural histories and treatment regimens. Seropositivity for NMO-IgG and longitudinally extensive spinal cord lesions are characteristic of NMO. Despite the absence of a definitive therapeutic strategy for NMO syndrome, methylprednisolone pulse therapy is recommended in the acute phase. Treatment strategies in relapse phases are aimed at preventing relapses, and increasing evidence shows a better clinical response of immunosuppressive therapy than immuno-modulating therapy (a standard multiple sclerosis-modulating therapy). We have described a 32 years old girl who had visual loss due to acute optic neuritis before 15 days in right eye and followed by complete visual loss in left eye. NMO was diagnosed because of its characteristic longitudinal myelitis and positive NMO-IgG. After combine therapy with prednisolone and an immunosuppressant, the patient’s medical condition was stable and no relapse symptoms were observed.